A good kind of trouble - Ramée, Lisa Moore (Balzer + Bray, 2019)
All twelve-year-old Shayla wants to do is follow the rules, but when she starts seventh grade, the rules have changed. Her two best friends seem to be going their own ways and some people at school are saying that she's not black enough. After a ruling in a controversial court case involving the shooting of a black man by a white police officer, Shayla decides to join the Black Lives Matter movement and begins passing out black armbands at school. As the unrest in both Los Angeles and her school spreads, Shayla must figure out if some things are worth breaking the rules.